Effects of Corruption on Basic Education Administration in Nigeria and the way Forward - Ogunode Niyi Jacob; Shofoyeke Adetunji Stephen (Researchparks Publishing, 2021)
Corruption in Nigeria is a hydra-headed and multi-facet problem that ramifies every sector of our national life and the education sector has not being innocent. Corruption have penetrated the Nigerian education system including the Basic education administration. This article discussed the effect of corruption on Basic education administration in Nigeria. Secondary data were used to support the points raised in the article. The secondary data were sourced from print material and online publication by recognized institutions and individual authors. This paper identified; shortage of funds, inadequate teachers, shortage of infrastructural facilities, poor quality of education, large out of school children, poor capacity development, poor implementation of Basic education policies and increase in the cost of Basic education administration as the effects of corruption on Basic education administration in Nigeria. To address these problems, the paper suggested that the government among other suggestion should establish anti-corruption units in the ministries and agencies of education to help check mate corrupt practices among staff and ensure regular auditing of commissions, agencies and ministries of education account could help check financial corruption within the system.